Pengaruh Teknik Membaca Skimming Terhdap Kecepatan Efektif Membaca Pada Siswa Kelas X SMA Negeri 1 Pekalongan - Annisa, Syafria Rahma; Riadi, Bambang; Prasetya, Rian Andri (Stilistika : Journal of Indonesian Language and Literature, 2023)
This study aims to determine the effect of skimming techniques on the effective reading speed of students at SMA Negeri 1 Pekalongan. The method used in this research is experiment. The subjects in this study were students of SMA Negeri 1 Pekalongan with a total sample of 50 students. The data collection technique used was a questionnaire, the data analysis technique used was descriptive statistical analysis. research shows that there are three hypotheses. The first hypothesis shows that there is a significant difference in the effective reading speed between the pre-test and the post-test in the experimental class, the second hypothesis shows that there is a significant difference in the effective reading speed between the pre-test and the post-test in the control class, the third hypothesis is carried out to find out effective reading speed ability between the experimental class and the control class. The results of the hypothesis testing carried out showed that the skimming technique was able to increase the effective reading speed of SMA Negeri 1 Pekalongan students in class X. This was also supported by the results of hypothesis testing that had been carried out between the experimental class and the control class. The results of testing the T-test hypothesis using the SPSS Statistics 25 program for windows can be seen that the value of T (Count) > T_Table is 2.782 > 2.060. This proves that there is a difference in the effective speed of reading in the experimental class and the control class.